Operationalization of the test and not treat strategy to accelerate the elimination of onchocerciasis and lymphatic filariasis in Central Africa - Kamgno, Joseph (Int Health, 2018)
After 30 years of treatment with Mectizan (ivermectin), cutaneous and ocular complications of Onchocerca volvulus infection are now scarce in endemic communities. Indeed, transmission has been interrupted and the O. volvulus- associated disease has disappeared in some African foci. Despite this success, onchocerciasis elimination in Loa loa co-endemic areas is still constrained by severe adverse events (SAEs) occurring after ivermectin treatment in some individuals harbouring very high L. loa microfilaremia. One approach towards the prevention of these SAEs is to identify individuals with high L. loa microfilaremia and exclude them from ivermectin treatment. The development of the LoaScope has provided the tool that underlies this test and not treat (TaNT) strategy. The first successful TaNT campaign was conducted in a L. loa highly endemic focus in Cameroon in 2015 without any SAEs. To accomplish this within a research setting, 60 people were deployed for this campaign, making this ‘research’ strategy not sustainable from a cost perspective. We describe here a way of reducing the cost of the TaNT strategy with a smaller team (three people) selected within affected communities. We also suggest the organization of a TaNT campaign in affected countries.